Cryopreservation as an assisted reproductive technology - I. R. Abdulazimova; L. L. Mezhidova; R. S. Barkinkhoeva; Z. U. Zarieva; Z. Kh. Abadieva; Kh. R. Magamadova; A. L. Vazikaeva; A. A. Bzhekshieva; D. A. Bogatyreva; E. A. Kauts; M. A. Bayanova; Kh. U. Umarova; et al. (Акушерство, гинекология и репродукция, 2020)
Introduction. According to the World Health Organization, infertility affects approximately one in six reproductive-age people. Assisted reproductive technologies (ART), particularly in vitro fertilization (IVF), have been available for more than three decades and have resulted in the birth of millions of children worldwide. Cryopreservation allows for the storage of large numbers of cells and tissues and is used in medicine for various purposes, including IVF.Aim: to analyze literature-based data on physical principles, methods, and prospects of cryopreservation in reproductive medicine.Materials and Methods. A review of scientific publications reported by domestic and international authors was conducted using the PubMed/MEDLINE, Google Scholar, and eLibrary databases from 1953 to September 2024. The following keywords were retrieved: “infertility”, “assisted reproductive technologies”, “in vitro fertilization”, “cryopreservation”, “cryoprotectants”, “cryoprotective agents”, “vitrification”, “gamete selection”, “sperm cryopreservation”, “female gamete cryopreservation”, “embryo cryopreservation”. There were predominantly reviewed full-text articles in Russian and English published in peer-reviewed scientific journals, containing original data or systematic analysis, as well as information on the effectiveness, safety, and biological impact of cryopreservation methods. For historical and contextual coverage of the topic, selected monographs, reviews, regulatory documents, and conference materials were also used, provided their relevance to the subject matter. These sources were not included in the assessment of method effectiveness but were considered in the context of the timeline for the technologies and ethical-legal aspects. A total of 5,876 publications were analyzed, of which 74 were included in the final review.Results. The physical and chemical principles of cryopreservation, classification of cryoprotective agents (CPA), as well as comparative effectiveness for various freezing methods (slow, rapid, ultra-rapid, and vitrification) were systematized. It was established that vitrification provides the highest survival rates for oocytes and embryos compared to conventional freezing, particularly when high-concentration CPAs are used in combination with non-penetrating agents. An effect of alternative carriers and biomaterials (e.g., hyaluronan-phenolic hydroxyl microcapsules, Volvox globator) for single-sperm cryopreservation was examined. Approaches to assessing gamete quality after thawing were summarized, including promising methods such as cell-free DNA analysis and the application of artificial intelligence for embryo morphology assessment. Unresolved issues were identified, including high CPAs-related toxicity, lack of standardized clinical protocols, as well as ethical and legal concerns regarding cryomaterial handling. The need for further research aimed at developing safe and effective ART-related cryopreservation protocols is emphasized.Conclusion. The analysis revealed knowledge gaps related to the optimization of clinical cryopreservation protocols for embryos and female gametes. Currently, vitrification remains the preferred method, providing the highest survival rates for biological material.